2022
DOI: 10.3390/land11020280
|View full text |Cite
|
Sign up to set email alerts
|

Towards Sustainable Urbanization: Exploring the Influence Paths of the Urban Environment on Bidders’ Collusive Willingness

Abstract: Collusive bidding is a severe unethical and illegal practice in urban construction projects. This practice has been identified as the primary inhibitor of sustainable urban development. Collusive bidding is formed and can be profoundly impacted by the urban environment. Identifying the transmission routes of the impacts of the urban environment on collusive bidding is conducive to urban governors formulating collusive governance countermeasures to create a healthy pace of urbanization. Therefore, this study ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…For cities with a poor collusion environment, the government should strengthen its management efforts and try to reduce the tendency of social collusion and destroy the collusion environment through strong and effective control measures (such as increasing the enforcement of policies and implementing regular inspection measures); and build a social environment in which "collusion is not possible, not daring to collude, and not wanting to collude" in phases. The government should build a social environment in which people cannot, dare not, and do not want to collude [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For cities with a poor collusion environment, the government should strengthen its management efforts and try to reduce the tendency of social collusion and destroy the collusion environment through strong and effective control measures (such as increasing the enforcement of policies and implementing regular inspection measures); and build a social environment in which "collusion is not possible, not daring to collude, and not wanting to collude" in phases. The government should build a social environment in which people cannot, dare not, and do not want to collude [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, local governments should take the local market environment and project types into consideration and reasonably regulate the competition level of projects for different project types to control the collusion phenomenon. Furthermore, the government's guiding role should be fully exerted to realize the synergistic control of internal and external environments [43][44][45].…”
Section: Plos Onementioning
confidence: 99%
“…The world population has grown significantly and our economies have become more industrialized over the past few hundred years, and, as a result, many more people have moved into cities [1,2]. This process is known as urbanization [2,3]. As shown in the statistic, the degree of urbanization in China, the world's second-largest economy, rose from 36 percent in 2000 to around 63.89 percent in 2020 [2].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Owusu et al [5] found that severe corruption behavior in the urban construction process weakened urban environmental management and increased urban susceptibility to extreme impacts of natural and human-made disasters. Wang et al [3] demonstrated that collusive bidding is the most severe and illegal behavior in urban construction projects. Widespread collusive bidding has been identified as the primary inhibitor to the health and sustainability of urban development [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation